Phenomenon of Inbreeding Depression on Maize in Perspective of The Quran - Ali, Mudzakkir; Kuswanto, Kuswanto; Kustanto, Heri (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
The objectives of this study were to learn and prove the truth and scientific miracles of The Quran, specifically the prohibition of incest for humans, also applies and affects especially on the growth and yieldin particularly open pollinated plants such as maize through the process of inbreeding depression. The results of yield of each genotype of the tested inbred line showed yield reduction in all inbred lines tested from generation of S1 to S5. Lamuru and Bisma which were generated with an open pollinated breeding produced relatively stable yield from generation of S1 to S5. The entire tested inbred lines showed some trait changes, such as height of crop (cm) and yield of grains (t/ha) that tended to decline and die, while Lamuru and Bisma tended to be stable. It is implied in letters of The Quran, which forbid inbreeding for human that is very detrimental, not only on life sustainability of human beings and animals, but also on plants, particularly on the cross-pollinated plants. The scientific truth of The Quran which prohibits incest for humans are proven to be identical and also apply in maize.